Does operating performance really improve following corporate acquisitions? - Ghosh, Aloke (Journal of Corporate Finance, 2001)
Previous research indicates that operating performance improves following corporate acquisitions relative to industry-median firms. Such performance results are likely to be biased because acquiring firms undertake acquisitions following a period of superior performance and they are generally larger than industry-median firms. Using firms matched on performance and size as a benchmark, I find no evidence that operating performance improves following acquisitions. I also analyze if performance is higher in cash acquisitions as suggested by various studies. The results indicate that cash flows increase significantly following acquisitions that are made with cash, but decline for stock acquisitions.